Farm2Fork through the lens of community ecology: concepts and applications in postharvest storage - Gerken, Alison R.; Morrison, William R. (Frontiers in Sustainable Food Systems, 2023)
The environment in which postharvest crops are processed and stored is a dynamic ecosystem influenced not only by environmental factors such as temperature and humidity, but also by biotic influences such as humans and insects. Abiotic influences such as variation in landscapes of warehouses, processing facilities, storage and shipping containers, and urban and agricultural settings can also drive changes in ecosystem processes for insects living in a postharvest system. Principles of community ecology can help to tease apart broad interactions among the environment including succession, interactions with conspecifics that lead to competition and niche partitioning, behavioral ecology variation, and physiology and developmental changes. Focusing on these concepts for integrated pest management (IPM) for stored product insect pests can help pest managers to better predict risk thresholds and develop targeted approaches for treatments. Typically, pest management decisions focus on single species without regards to the interactions with other species. Without consideration of the entire ecosystem, targeted treatments for one species can have both direct and indirect impacts on other species that may have equally detrimental effects on stored products. Current knowledge of stored product ecosystems lags behind what is known for field pest ecosystems, and hinders our ability to design effective control strategies for the whole system. Here, we present a review of work on stored product insect pests using a community ecology lens. We analyze how the current state of the knowledge regarding species interactions and variation and incorporating factors such as movement, species interactions, energy transfer models in succession, behavior, and effects of climate change in ecological modeling can be used to better develop and implement more effective postharvest IPM. Implementing these concepts will significantly improve management of these insects and can help reduce time and cost associated with managing and treating insect infestations.